Regional oceanography affects humpback whale entanglements in set fishing gear - Schilling, HT; Dedden, AV; Crocetti, S; Liggins, G; Lorigan, S; Marshall, A; Rogers, TL; Schaeffer, A; Suthers, IM; Johnson, DD (Conservation Science and Practice, 2023)
Humpback whales Megaptera novaengliae undertake annual migrations along eastern Australia, where they can be susceptible to entanglement in set fishing gear. This can potentially result in both sublethal and fatal outcomes for the whales, and financial losses for the fishing industry, including loss of gear and catch. Interannual fluctuations in entanglement records suggest that dynamic oceanographic features may be associated with the whales' migration path, and therefore, risk of entanglement. Using records of demersal fish traps off the coast of New South Wales (NSW), we identify two areas of high fishing pressure and entanglement risk overlap. Within each area, we combine entanglement observations with metrics associated with the East Australian Current (EAC) and climate (i.e., southern oscillation index). We show that the strength and position of the EAC was associated with the likelihood of entanglement in set fishing gear. In northern NSW (30.3° S), entanglement risk was highest between July and October when the EAC is relatively close to the coast. In contrast, there was no evidence suggesting that oceanography further south in the separation zone of the EAC (33.8° S) was associated with risk of entanglement. In the years following a strongly negative SOI (i.e., El Niño events), entanglement risk was also reduced. While we provide clear linkages with regional oceanographic dynamics and entanglement risk off NSW, if a dynamic ocean management approach to reducing entanglements is to be realized, further research into the fine-scale movements of humpback whales is needed.